2021
DOI: 10.1177/1548512920982673
|View full text |Cite
|
Sign up to set email alerts
|

Real-time calculation of the initial angle of projection for fragments in cylindrical warheads

Abstract: This paper presents an improvement in the speed and accuracy of calculating the initial angle of projection of fragments for exploding cylindrical shells. It is a fast tool that can be used by designers, where existing approaches, such as computationally intensive Finite Element Analysis, are preventively slow. An enhanced Taylor equation is presented using available experimental data and the effect of the changing shape of the warhead’s cylindrical casing on the fragment’s initial projection angle. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…e average error of the two warhead samples is within ±7%. e calculated model data in this paper are compared with flying angle prediction results of Taylor and Flix et al [7,8] formulas, and the comparison results are shown in Figure 14. e prediction of the fragment's flying angle given by the Taylor formula was close to a straight line parallel to the X/L axis.…”
Section: Model Verification Error Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…e average error of the two warhead samples is within ±7%. e calculated model data in this paper are compared with flying angle prediction results of Taylor and Flix et al [7,8] formulas, and the comparison results are shown in Figure 14. e prediction of the fragment's flying angle given by the Taylor formula was close to a straight line parallel to the X/L axis.…”
Section: Model Verification Error Analysismentioning
confidence: 99%
“…where D is the detonation velocity of the explosive, and θ/2 is the angle between the fragment's flying direction and the normal direction of the projectile body, which is called the "Taylor angle." Figure 1 is adapted from Felix et al [8], Carlucci and Jacobson [9], Deshpande [10], and Walters and Zukas [11], representing the variables in the Taylor formula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial angle of projection of a fragment depends on the Taylor angle, developed in Felix et al’s paper 12 and shown in the following equation:…”
Section: Approachmentioning
confidence: 99%
“…where t is a constant. Equation (12) has different values of t to determine different points on the straight line. Then, using Figure 7, the coordinates of the fragment rotated about the edge on the casing are (x 1 + L L sinα, Figure 10 shows the Y and Z coordinates of the fragment about to be projected.…”
Section: Calculate Where Fragments Hit the Targetmentioning
confidence: 99%